Irritation fibroma of tongue: a case report - Vujhini, Sudhir Kumar; Reddy, E. Sridhar; Sudheer, M.V.S.; Katikaneni, Hari Krishna (International Journal of Research in Medical Sciences, 2016)
Reactive hyperplastic outgrowths are seen in the oral cavity due to chronic irritation by plaque, calculus, overhanging margins, trauma and dental appliances. Irritation fibroma represents a reactive focal fibrous hyperplasia due to trauma or local irritation. We report a case of irritation fibroma of right lateral border of tongue in a 46-year-old female.